Revisiting John Chrysostom’s Interpretation of the Relationship between Abram and Lot and Their Separation in LXX Genesis 12–13 - De Wet, Chris L. (Journal for semitics, 2023)
This article revisits and examines more closely John Chrysostom’s (ca. 349-407 CE) characterisation of Lot—specifically his relationship with Abram and their separation in LXX Gen 12-13—as an exemplar to think about early Christian social relations. This study forms part of a larger project investigating Chrysostom’s use of Old Testament exemplars in his preaching and moral instruction. It is shown that the formulation of early Christian social ideals was mediated by means of scriptural exemplars like Lot. Rickett’s (2019) descriptive analysis of Chrysostom’s reconstruction of Lot’s character in Gen 13 is a useful trajectory for this study. However, while Rickett explains in detail what Chrysostom thought about Lot’s separation from Abram (and how this differs or concurs with other interpreters), he does not discuss why Chrysostom reconstructs the character of Lot in the way he does. This is the purpose of this study—to ask more pertinent questions on why Chrysostom wants to safeguard Lot’s reputation and, more generally, why he was such a useful exemplar in early Christian biblical interpretation.